Vector surveillance of avian Plasmodium and West Nile virus in Culex mosquitoes from Doñana, a UNESCO World Heritage Site - Josué Martínez-de la Puente; Juliana Tamayo-Quintero; María José Ruiz-López; Jesús Veiga; Santiago Ruiz; Ana Vázquez; Laura Herrero; Ramón C. Soriguer; Jordi Figuerola (Parasites & Vectors)
Abstract Background Mosquito-borne pathogens produce relevant diseases causing human fatalities worldwide. In addition, mosquitoes transmit a variety of pathogens to livestock and wildlife, negatively affecting local economies and causing ecological impacts. Methods Mosquitoes collected in a highly protected wetland from southern Spain were molecularly screened for the presence of three major pathogens, including the zoonotic flavivirus West Nile virus (WNV), avian Plasmodium, and filarioid nematodes. Results Overall, 95 mosquito pools including 1376 females corresponding to 4 Culex species were molecularly analyzed, including 40 mosquito pools containing 390 Culex pipiens, 42 mosquito pools containing 880 Culex perexiguus, 10 mosquito pools containing 102 Culex modestus, and 3 mosquito pools containing 4 Culex laticinctus. WNV was detected in 5 Cx. perexiguus pools. Avian Plasmodium was found in 28 mosquito pools tested, including 17 pools of Cx. perexiguus and 11 pools of Cx. pipiens. Three different Plasmodium spp. lineages were found in mosquitoes, corresponding to the morphospecies: P. vaughani (SYAT05; n = 22), P. matutinum (LINN1; n = 4), and the Plasmodium sp. (SGS2; n = 1). One positive sample was not identified at the lineage level. Plasmodium prevalence was significantly associated with mosquito species and sampling session and marginally related with mosquito pool size. None of the pools tested were positive for the presence of Dirofilaria spp. Conclusions These results represent the most taxon extensive survey of pathogens in mosquitoes in Doñana. This study expands the knowledge of the diversity of pathogens naturally circulating in this protected wetland in southern Spain. Recommendations for the population are considered. Graphical Abstract